A conceptual framework for Islamic institutional and retail investment in maritime assets - Abdullah, Adam; Hassan, Rusni; Kassim, Salina (CCSE, 2018)
The purpose of this research is to provide a conceptual framework for Islamic institutional and retail investment in maritime assets. Our objectives are to provide an introduction to seaborne trade and analyze trends in institutional interest in alternative assets and international shipping as well as highlight Islamic and conventional equity structures for institutional and retail investors. Our findings reveal that an Islamic private equity framework involving an unlevered, tax-free investment in maritime assets provides a real alternative to conventional lending and even successful tax-efficient conventional equity structures, since they are not entirely without issues given the significant presence of debt financing from maritime banks. There is a demand for alternative sources of finance, such that Islamic equity finance, rather than conventional lending or structured debt can develop international shipping involving Islamic institutional and retail investment in maritime assets.